SOCIAL ENVIRONMENTAL AND ECONOMIC STUDY OF FAMILY PRODUCTION OF THE BEEKEEPERS COOPERATIVE OF CATOLE DO ROCHA- PB - Bezerra Ferreira, Mayra Linhares; Arnaud, Edinaldo da Rocha; Leite, Delzuite Teles; Sousa, Luci Cleide Farias Soares; Schmidt Filho, Ricardo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
The cooperatives and beekeeping activity play a key role in social and economic development of small producers, therefore aimed to study the environmental and socio-economic development of family farming cooperative of beekeepers in the municipality of Catole do Rocha, PB. The study was conducted in the microregion of Catole do Rocha in Paraiba State. Data were obtained through questionnaires and semi-structured, applied directly to the farmers and leaders, in this case, the presidents of associations of beekeepers of the communities studied. Data from the survey were analyzed using percentage calculations. Beekeepers associated are the proper community, or from the rural area of another municipality, showing a very small illiteracy rate, and even producers with higher education. The agricultural activities represent only 20% of average household income and the non-agricultural sources of income more frequent retirement or pension. The productivity and credibility of beekeeping have been growing considerably in recent years; there is an increased diversity of products and processing of honey. The institution currently more active in encouraging beekeeping is SEBRAE, and others like EMBRAPA and SENAR. Sustainability of activity were obtained average values, above average, but still not satisfactory, being necessary support measures and training for these producers especially in regard to preserving the environment.